2022
DOI: 10.1071/am21040
|View full text |Cite
|
Sign up to set email alerts
|

Factors that drive koala roadkill: an analysis across multiple scales in New South Wales, Australia

Abstract: A challenge to understanding the impacts of roads on koalas is that their effects operate across multiple scales. To determine what conditions underlie koala roadkill, we looked at koala roadkill at two spatial scales – the entire state of NSW, and a local government area (Coffs Harbour) – for three road types (primary, arterial and local). We also subdivided the state data into three regions – coast, tableland and inland – to look at regional differences. Our analyses show that koala roadkill is ubiquitous ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Drought has been experienced in numerous parts of Australia in recent years; drought can depress koala populations (Gordon et al .1988) and compounds the loss due to fire (Lunney et al . 2020). This was not studied here, but we acknowledge that drought could have affected our sites differently.…”
Section: Discussionmentioning
confidence: 99%
“…Drought has been experienced in numerous parts of Australia in recent years; drought can depress koala populations (Gordon et al .1988) and compounds the loss due to fire (Lunney et al . 2020). This was not studied here, but we acknowledge that drought could have affected our sites differently.…”
Section: Discussionmentioning
confidence: 99%
“…Road mortality is a significant threat to wildlife populations (Fahrig and Rytwinski 2009) including koalas across their range (Lunney et al 2022a(Lunney et al , 2022bMelzer and Black 2022), with a reported 300 vehicle related deaths per year in South East Queensland alone (Dique et al 2003b;de Oliveira et al 2014). Major roads, with higher volumes and speeds of traffic can act as movement barriers, decreasing habitat connectivity and gene flow (Dudaniec et al 2013).…”
Section: Roads As a Major Anthropogenic Threatmentioning
confidence: 99%
“…Koalas in both urbanised and rural environments are at risk from mortality related to vehicular collisions (Dique et al 2003;Rhodes et al 2014;Gonzalez-Astudillo et al 2017;Lunney et al 2022aLunney et al , 2022b, but our results predict that the management of vehicle strike hotspots is likely to be more effective in the Hinterland and Riverine landscapes than in the Coastal landscape. Although it was not possible to validate model predictions against empirical data, the results accurately reflect the best guess of experts in the area.…”
Section: Discussionmentioning
confidence: 63%
“…This model considered the recognised top six local management actions to address those threats. We have not included climate-related threats, such as drought, fire and heatwaves (Lunney et al 2012(Lunney et al , 2020, and although some mitigation is possible at the local level, long-term management actions to address these broad and globally important issues require input at state, national, and international levels. We have addressed those threats that have been identified as most relevant when mitigation actions are implemented at a local or regional scale.…”
Section: Discussionmentioning
confidence: 99%